2011
DOI: 10.2169/internalmedicine.50.4779
|View full text |Cite
|
Sign up to set email alerts
|

Resting Metabolic Rate and Anthropometric Measurements in Male Sleep Apnea Patients

Abstract: Objective Obstructive Sleep Apnea Syndrome (OSAS) is a common sleep-related breathing disorder. Associations among Apnea-Hypopnea Index (AHI), Resting Metabolic Rate (RMR), body habitus differences, and otorhinolaryngologic abnormality may clarify the characteristics of patients with OSAS. In order to test this hypothesis, we aimed to compare the RMR, Modified Mallampati Scores (MMS), anthropometric measurements and body composition of male OSAS patients with simple snorers and to investigate the association a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
0
25
1
1
Order By: Relevance
“…However, in the resulting the agreements, substantial differences were observed between the methods. The relationship between OSA and obesity has been extensively studied in recent years (2,3), and the effects of OSA on energy expenditure have been a target of some studies (5,6,13). In contrast with previous studies that suggested that REE is increased in OSA patients, our study doesn't confirm any effect of OSA severity on REE.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…However, in the resulting the agreements, substantial differences were observed between the methods. The relationship between OSA and obesity has been extensively studied in recent years (2,3), and the effects of OSA on energy expenditure have been a target of some studies (5,6,13). In contrast with previous studies that suggested that REE is increased in OSA patients, our study doesn't confirm any effect of OSA severity on REE.…”
Section: Resultscontrasting
confidence: 96%
“…Oxyhemoglobin desaturation, successive arousals, and continuous sympathetic activation might be responsible for enhanced metabolism in OSA patients (5,6). OSA also leads to elevated diurnal somnolence and fatigue, which contributes to a sedentary lifestyle and decreased PAEE.…”
Section: Introductionmentioning
confidence: 99%
“…OSA may also affect energy metabolism. RMR [54], sleeping EE [55] and 24-h EE are increased in OSA patients compared to snoring controls [56]. In another study, resting EE was found to be independently and positively associated with AHI even after adjusting for BMI [57] or fat-free mass [58].…”
Section: Mechanistic Insights: Impact Of Sleep On Energy Balancementioning
confidence: 99%
“…In terms of energy expenditure, OSA appears to be characterised by lower levels of physical activity, as assessed subjectively by questionnaire [22] and objectively using accelerometry [23]. In addition, OSA may affect energy metabolism, with reports of elevated resting metabolic rate (RMR) [24], sleeping energy expenditure [25] and 24-h energy expenditure in patients versus controls [26]. …”
Section: Introductionmentioning
confidence: 99%